TREATMENT OF MALASSEZIOSIS IN MIXED BREED DOGS USING A COMBINATION OF ORAL AND TOPICAL THERAPY - Kadek Ferdy Agastia Dwi Pratama; Putu Ayu Sisyawati Putriningsih; I Putu Gede Yudhi Arjentinia (Buletin Veteriner Udayana, 2025)
The integumentary system is the body's outer defence system that functions as a defence system against temperature, foreign substances, and fungal, bacterial, and parasitic infections. The purpose of writing this article is to provide information about the causes and impacts of Malassezia fungal infections and their treatment. In normal skin function, there is a group of normal microorganisms that grow on the surface of the skin that can be components and indicators in determining skin health. Malassezia fungi are fungi in the form of yeast or mycelium that live in areas of the body that are rich in sebaceous such as the back, chest, and head. A number of diseases that originate from the pathogenicity of Malassezia fungi are interpreted as malasseziosis which causes many symptoms such as hyperpigmentation or hypopigmentation, scaly skin, itching. Malassezia infection is interpreted as a decrease in the immune system such as the complement system, cellular immune response, and humoral immune response. The diagnostic method for malasseziosis in dogs requires thorough observation of the distribution of lesions such as alopecia lesions, pruritus, hyperpigmentation, hyperkeratosis, and crusts. The necessary supporting examinations such as Wood's lamp and tape acetate. Morphologically, observations were made using a microscope with a magnification of 1000Χ by observing the results of acetate tape that had been stained with diff-quick by looking at the shape of the Malassezia fungus like a round shoe sole. Post-infection control and treatment were given systemically and topically through the use of oral ketoconazole agents, symptomatic treatment of pruritus with chlorpheniramine maleate, and supportive with fish oil, vitamin CDE, and mineral Z.